Authentically Jewish : Identity, Culture, and the Struggle for Recognition - Charmé, Stuart Z. (Book collections on Project MUSE., 2022)
This book analyzes the different conceptions of authenticity that are behind conflicts over who and what should be recognized as authentically Jewish. Although the concept of authenticity has been around for several centuries, it became a central focus for Jews since existentialist Jean-Paul Sartre raised the question in the 1940s. Building on the work of Sartre, later Jewish thinkers, philosophers, anthropologists, and cultural theorists, the book offers a model of Jewish authenticity that seeks to balance history and tradition, creative freedom and innovation, and the importance of recognition among different groups within an increasingly multicultural Jewish community. Author Stuart Z. Charmé explores how debates over authenticity and struggles for recognition are a key to understanding a wide range of controversies between Orthodox and liberal Jews, Zionist and diaspora Jews, white Jews and Jews of color, as well as the status of intermarried and messianic Jews, and the impact of Jewish genetics. In addition, it discusses how and when various cultural practices and traditions such as klezmer music, Israeli folk dance, Jewish yoga and meditation, and others are recognized as authentically Jewish, or not.